Preliminary Screening of South African Plants for Binding Affinity to the Serotonin Reuptake Transporter and Adenosine A1/A2A Receptors - Andisiwe Mnqika; Adeyemi O. Aremu; H. D. Janse van Rensburg; Makhotso Lekhooa (MDPI AG, 2023)
In South African traditional medicine, Gomphocarpus fruticosus (L.) W.T. Aiton, Hypoxis hemerocallidea Fisch. & C.A. Mey., and Leonotis leonurus. (L.) R.Br. have been recorded among different ethnic groups to be a valuable herbal remedy for the management of depression-related conditions. The current study investigated the affinity of these three plants toward the serotonin reuptake transporter (SERT) and adenosine A1/A2 receptors. Six solvents (water, methanol, acetone, dichloromethane, petroleum ether, and hexane) were used to extract the selected plants. We established that eight extracts exerted potential affinity based on the applied in vitro binding experiment. The methanol and acetone extracts of Hypoxis hemerocallidea had 60% specific binding of [3H]citalopram, an indication that almost 40% of the plant extracts were bound to the SERT. For the adenosine receptor binding assays, methanol and hexane extracts of Leonotis leonurus were the most active, with rA1Ki values of 0.038 and 0.176 mg/mL, respectively. In addition, the dichloromethane extract of Gomphocarpus fruticosus had an rA1Ki value of 6.46 mg/mL. Extracts from the more polar solvents methanol and dichloromethane had higher binding affinity. Additionally, these plant extracts acted as antagonists at the adenosine A1 receptor. Overall, the current findings provide an indication of the potential antidepressant effects of some of the tested extracts based on their binding to the receptors evaluated. However, a combination of other in vitro assays is needed to establish possible mechanisms of action. In addition, computational analysis and profiling of plant extracts is crucial to identify the bioactive compounds with a higher affinity to the receptors. Ultimately, in vivo studies remain essential to allow for an in-depth elucidation of the mechanisms of action.